Analisis Faktor-faktor yang Mempengaruhi Minat Masyarakat Menabung di Bank Syariah Indonesia: Studi pada Masyarakat Kota Bandung - Ghojali, Irman; Suryaman, Maman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Islamic banking is an Islamic economic phenomenon that has become an alternative and increasingly popular with people around the world, including millennials. Not only to accommodate the interests of Muslims, but also to integrate personal interests and community benefits in a balanced form. Islamic banking in Indonesia is currently experiencing rapid development. As a country with the largest Muslim population in the world, Indonesia certainly has a very important role in building the Islamic economy. This can be used as a great opportunity by Bank Syariah Indonesia in optimizing its role to support the country's plan to develop Islamic finance in Indonesia. It can be seen that the number of customers at Bank Syariah Indonesia is still far from expectations when viewed from the large Muslim population in Indonesia. This indicates that there are still many Muslim residents in Indonesia who still do not use the services of Sharia Banks in Indonesia. This indicates that there are still many Muslim residents in Indonesia who still do not use the services of Sharia Banks in Indonesia. This can arise by several factors that are the reason why the Indonesian Muslim population is still reluctant to use the services of Bank Syariah Indonesia. The large gap between the Muslim population in Indonesia and the number of customers of Bank Syariah Indonesia is one of the attractions for researchers to conduct an analysis of the Factors Influencing Public Interest in Saving at Bank Syariah Indonesia (BSI). Interest can be interpreted as an interest or tendency to choose what is desired. One example is the interest and tendency towards interest in saving, for example a religiously inclined person will choose Islamic banks over conventional banks because based on Islamic religious law which prohibits his people from transacting ribawi (interest). According to (crow & crow 1998) states that there are six that affect interest, namely: income factors, job stability factors, financial goal factors, risk avoidance factors, knowledge factors, social and cultural environmental factors. While the author in conducting this study used descriptive qualitative methods with data collection techniques used was to conduct structured interviews to the community with the help of research instruments in the form of mobile phone cameras as photo documentation and recordings during interviews with the people of Bandung City which at this time became a source of research information. The results obtained from research conducted by the author to the people of Bandung city resulted in income, risk avoidance / security factors and social and cultural environmental factors are factors for people interested in saving their money in Indonesian Islamic banks (BSI). Keywords: Bank Syariah Indonesia, community, Interest.